OS POVOS INDÍGENAS DA AMÉRICA LATINA EM RISCO: UM ESTUDO SOBRE AS TRIBOS ACHUAR, AYMARA E QUÉCHUA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
Indigenous peoples have historically been victims of the State because, through the institutions that, theoretically, would have the task of representing them in the political, administrative, legal and legislative spheres, they act, for the most part, based on economic interests and leaving the individual, collective, cultural, social and environmental rights of such peoples at the margin, especially in Latin America. We emphasize the importance of the indigenous presence in the first centuries until the alarming increase in cases of invasions of land, illegal exploitation of natural resources, the omission of the government in combating pandemic diseases, and the various damages to the heritage of indigenous peoples, particularly the Achuar, Aymara, and Quechua peoples. It can be said that these peoples are more than survivors, because after centuries of persecution and disrespect, they still preserve their rich cultures, which can and should be used to guide the course of the countries they inhabit.